Earnings Risk and Demand for Higher Education: A Cross-Section Test for Spain - Joop Hartog; Luis Diaz Serrano (Institute for the Study of Labor (IZA), 2002)
We develop a simple human capital model for optimum schooling length when earnings are stochastic, and highlight the pivotal role of risk attitudes and the schooling gradient of earnings risk. We use Spanish data to document the gradient and to estimate individual response to earnings risk in deciding on attending university education, by measuring risk as the residual variance in regional earnings functions. We find that the basic response is negative but that in households with lower risk aversion, the response may be reversed to positive.
Keywords: I21; 330; earnings risk; schooling decisions; Bildungsverhalten; Studium; Verdienstausfall; Einkommen; Risiko; Schätzung; Spanien